Insights into purification of contaminated water with activated charcoal derived from hamburger seed coat - Ajala, L.O; Ali, E.E.; Obasi, N.A.; Fasuan, T.O.; Odewale, I.O.; Igidi, J.O; Singh, J. (Springer Science and Business Media Deutschland GmbH, 2022)
Hamburger seed coat is a readily available agricultural waste product generated in large quantities annually. In this study, activated charcoal was produced using hamburger seed coat activated with zinc chloride and its physicochemical properties such as fixed carbon, specific surface area, volatile matter, ash and moisture content were investigated. Scanning electron microscopy and Fourier transform infrared spectrometry techniques were used to study the surface morphology and variations in the absorption bands of functional groups, respectively. The adsorbent biosorption of pollutants abilities from contaminated water was investigated using standard methods with a view to ascertaining the adsorbent purification potential. The results showed that the adsorbent was of high porous structure with adsorption capacity significantly correlated with iodine value. The physicochemical properties of the contaminated water treated with the adsorbent were comparable with commercial activated charcoal (control)-treated water but indicated a significant decrease (p < 0.05) in the pH, temperature, total dissolved solids, total suspended solids, conductivity, turbidity, alkalinity, hardness, biochemical oxygen demand, chemical oxygen demand, anions and heavy metal ions when compared to the untreated water. With the exception of alkalinity, other parameters investigated in the water treated with the test adsorbent fell within the standards set for potable water. Results of this study therefore revealed possibility of converting large quantities of hamburger seed coat wastes that could constitute environmental pollution to a profitable product that could be employed for treatment of wastewater
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Absorption spectroscopy; Activated carbon; Agricultural robots; Agricultural wastes; Alkalinity; Biochemical oxygen demand; Chlorine compounds; Dissolved oxygen; Fourier transform infrared spectroscopy; Heavy metals; Metal ions; Morphology; pH; Physicochemical properties; Potable water; Purification; Scanning electron microscopy; Surface morphology; Wastewater treatment; Water pollution; Water treatment plants; Zinc chloride; Adsorption capacities; Contaminated water; Environmental pollutions; Fourier transform infrared spectrometry; Porous structures; Total dissolved solids; Total suspended solids; Volatile matters; Chemicals removal (water treatment)